2020
DOI: 10.3390/su12124822
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in Higher Education: Impact on Student Motivation and the Acquisition of Social and Civic Key Competencies

Abstract: This study investigates to what extent the popular online gaming platform called Kahoot can be used as a creative and effective tool to promote motivation, engagement and meaningful learning. For this purpose, a quasi-experimental study was conducted with a sample of 101 undergraduate students of education who participated in online Kahoot quizzes by designing their own questions as part of the formative assessment. According to the results of the pre- and post-tests, the integration of this game-based student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0
25

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 33 publications
4
47
0
25
Order By: Relevance
“…Concerning the educational applications of gamification, the participants perceived that these applications in the classroom can contribute to the acquisition of skills, among which is learning to learn, digital skills, and social and civic values. These contributions are in line with other research [33,34], which indicates that gamification and the appropriate use of serious video games are key tools for teaching content, skills, abilities, and improving creative capacity. The study by Villalustre and Del Moral [32], carried out with students of the Degree in Pedagogy, obtained similar results, showing that the use of game dynamics applied in the realization of a project increased motivation, the level of satisfaction with the task entrusted, knowledge of theoretical contents, and the development of key generic competences.…”
Section: Discussionsupporting
confidence: 86%
“…Concerning the educational applications of gamification, the participants perceived that these applications in the classroom can contribute to the acquisition of skills, among which is learning to learn, digital skills, and social and civic values. These contributions are in line with other research [33,34], which indicates that gamification and the appropriate use of serious video games are key tools for teaching content, skills, abilities, and improving creative capacity. The study by Villalustre and Del Moral [32], carried out with students of the Degree in Pedagogy, obtained similar results, showing that the use of game dynamics applied in the realization of a project increased motivation, the level of satisfaction with the task entrusted, knowledge of theoretical contents, and the development of key generic competences.…”
Section: Discussionsupporting
confidence: 86%
“…Without the monograph from EKS in 2010, interest in the literature would not have been so strong. RPGs would have been found, especially compared with popularity of gamification [41,42,64], for example, with the use of Classcraft [7][8][9], or GBL. Both tendencies have a strong relationship with RPGs, a methodology with a huge potential in education [59].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, RPGs and gamification have several strong bonds [7][8][9]41,42,64]. This is another important issue regarding RPGs and education: how roleplaying games may be used in educational settings, inside game-based learning?…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are numerous works on the use of gamification in university education, particularly through the computer application Kahoot [14][15][16][17][18], that have obtained significantly positive results. D.T.A.…”
Section: Introductionmentioning
confidence: 99%
“…J.M. Campillo-Ferrer et al [15] examined the effect that a gamification activity based on Kahoot carried out in "Teaching Social Sciences", a second-year compulsory subject of the Primary Education degree at the University of Murcia, had on students' level of motivation and learning. They found that this teaching technique improved students' understanding of some concepts, increased their active participation in class and motivated them towards learning.…”
Section: Introductionmentioning
confidence: 99%